Robust adaptive distributed beamforming for energy-efficient network flooding - Abdelkader, Abdelrahman; Jorswieck, Eduard (EURASIP journal on wireless communications and networking, 2019)
In a device-to-device wireless multi-hop communication scenario with resource-constrained devices, the energy efficiency of communication plays a significant role in network design and operation. Based on the recently proposed Glossy network flooding approach, we introduce cooperation between transmitting nodes and formulate a robust multicast beamforming problem with imperfect channel state information (CSI) and analyze its performance. The level of cooperation is dependent on the number of limited feedback bits from receivers to transmitters. First, the impact of the number of limited feedback bits B on energy efficiency is studied, and the programming problem for finding the optimal B is formulated subject to a maximum outage constraint of 5%. Numerical simulations show that there exists an optimal number of feedback bits that maximizes energy efficiency. Second, the effect of the number of cooperating transmitters on energy efficiency is investigated. Results show that an optimum group of cooperating transmit nodes, also known as a transmit coalition, can be formed in order to maximize energy efficiency. Results show that the investigated techniques including optimum feedback bits and transmit coalition formation can achieve a 100% increase in energy efficiency when compared to the state-of-the-art Glossy under the same operation requirements in very dense networks.